Analisis Manfaat Penggunaan PLN Mobile Pada Bagian Pelayanan Pelanggan Di PLN ULP Medan Baru - Rizki Edom Noperion Manalu; Alya Al Haura; Adinda Eloyfani Ginting; Bella Amanda; Hania Syakira (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
In this era of globalization, business organizations must continue to improve the level of professional services in their respective fields. The use of PLN Mobile in the customer service department at PLN ULP Medan Baru has the potential to provide significant benefits in improving service quality and customer satisfaction. This application is expected to bring positive changes by providing easy access to information for customers regarding billing, blackouts, and other important information. The purpose of this research is to analyze the customer service and benefits of PLN Mobile at PLN ULP Medan Baru. This study uses a qualitative approach to explore an in-depth understanding of the benefits of using PLN Mobile in the customer service department at PLN ULP Medan Baru. A qualitative approach allows researchers to understand customer perspectives, views, and experiences in depth and contextually. Based on the results of the research and discussion conducted by the researchers, it can be obtained that the customer service and benefits of PLN Mobile at PLN ULP Medan Baru are quite good and very useful for customers at PLN ULP Medan Baru, Medan City to meet their electricity needs, complaints and complaints, however, socialization that has not been evenly distributed has resulted in there being PLN ULP Medan Baru customers who have not used the PLN Mobile application. The five dimensions of customer service used by researchers according to Tjiptono (2014: 18), namely the Tangibility, Reliability, Responsiveness, Assurance, and Empathy dimensions at PLN ULP Medan Baru are quite good.